2021
DOI: 10.3389/fpsyg.2021.564479
|View full text |Cite
|
Sign up to set email alerts
|

Toddlers Using Tablets: They Engage, Play, and Learn

Abstract: Although very young children have unprecedented access to touchscreen devices, there is limited research on how successfully they operate these devices for play and learning. For infants and toddlers, whose cognitive, fine motor, and executive functions are immature, several basic questions are significant: (1) Can they operate a tablet purposefully to achieve a goal? (2) Can they acquire operating skills and learn new information from commercially available apps? (3) Do individual differences in executive fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 79 publications
1
10
0
Order By: Relevance
“…Of the 53 studies included in the review, the majority originated from high‐income countries, most notably Western European countries (Bonneton‐Botté et al, 2020; Clarke & Abbott, 2016; Desoete & Praet, 2013; Di Lieto et al, 2017; Fernández‐Molina et al, 2015; Fikkers et al, 2019; Gremmen et al, 2016; Kiefer et al, 2015; Konok et al, 2021; Kosmas & Zaphiris, 2020; Mayer et al, 2020; Picard et al, 2014; Smeets & Bus, 2012; Teepe et al, 2017; Walter‐Laager et al, 2017), followed by the United States (Antrilli & Wang, 2018; Diehm et al, 2020; Haegele et al, 2011; O'Toole & Kannass, 2018; Parish‐Morris et al, 2013; Rogowsky et al, 2018; Russo‐Johnson et al, 2017; Schmitt et al, 2018; Schroeder & Kirkorian, 2016; Xu et al, 2021; Zhen, 2017; Zheng & Sun, 2021; Zimmermann et al, 2015), Australia (Axford et al, 2018; Barnett et al, 2012; Huber et al, 2018; McNeill et al, 2019, 2021; Neumann, 2014, 2016, 2018; Trost & Brookes, 2021), the United Kingdom (Bedford et al, 2016; Herodotou, 2018; Outhwaite et al, 2019; Portugal et al, 2021; Ross et al, 2016), Taiwan (Lin, 2019; Lin et al, 2017; Lin et al, 2020), and one study each from Canada (Courage et al, 2021), South Korea (Moon et al, 2019), and Israel (Elimelech & Aram, 2020). Only two studies were from middle‐income countries Brazil (Souto et al, 2020; Spinosa et al, 2020) and China (Hu et al, 2020; Liu et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the 53 studies included in the review, the majority originated from high‐income countries, most notably Western European countries (Bonneton‐Botté et al, 2020; Clarke & Abbott, 2016; Desoete & Praet, 2013; Di Lieto et al, 2017; Fernández‐Molina et al, 2015; Fikkers et al, 2019; Gremmen et al, 2016; Kiefer et al, 2015; Konok et al, 2021; Kosmas & Zaphiris, 2020; Mayer et al, 2020; Picard et al, 2014; Smeets & Bus, 2012; Teepe et al, 2017; Walter‐Laager et al, 2017), followed by the United States (Antrilli & Wang, 2018; Diehm et al, 2020; Haegele et al, 2011; O'Toole & Kannass, 2018; Parish‐Morris et al, 2013; Rogowsky et al, 2018; Russo‐Johnson et al, 2017; Schmitt et al, 2018; Schroeder & Kirkorian, 2016; Xu et al, 2021; Zhen, 2017; Zheng & Sun, 2021; Zimmermann et al, 2015), Australia (Axford et al, 2018; Barnett et al, 2012; Huber et al, 2018; McNeill et al, 2019, 2021; Neumann, 2014, 2016, 2018; Trost & Brookes, 2021), the United Kingdom (Bedford et al, 2016; Herodotou, 2018; Outhwaite et al, 2019; Portugal et al, 2021; Ross et al, 2016), Taiwan (Lin, 2019; Lin et al, 2017; Lin et al, 2020), and one study each from Canada (Courage et al, 2021), South Korea (Moon et al, 2019), and Israel (Elimelech & Aram, 2020). Only two studies were from middle‐income countries Brazil (Souto et al, 2020; Spinosa et al, 2020) and China (Hu et al, 2020; Liu et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Twenty‐nine studies were related to cognitive development (Table 5), of which 22 studies were Tier 1 (Antrilli & Wang, 2018; Chen et al, 2013; Courage et al, 2021; Desoete & Praet, 2013; Di Lieto et al, 2017; Elimelech & Aram, 2020; Fernández‐Molina et al, 2015; Haegele et al, 2011; Herodotou, 2018; Huber et al, 2018; Konok et al, 2021; Liu et al, 2021; Neumann, 2018; O'Toole & Kannass, 2018; Outhwaite et al, 2019; Parish‐Morris et al, 2013; Ross et al, 2016; Rogowsky et al, 2018; Schmitt et al, 2018; Schroeder & Kirkorian, 2016; Xu et al, 2021; Zhen, 2017), and seven studies were identified as Tier 2 (Fikkers et al, 2019; McNeill et al, 2019; McNeill et al, 2021; Neumann, 2014; Neumann, 2016; Neumann, 2018; Portugal et al, 2021; Russo‐Johnson et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, tablets are handy devices because they are flat and lightweight with built-in audio and video, which makes them easy to handle and employ in an interactive therapy setting with children. Learning via these devices can be very motivating for children, and there is growing evidence that they can be beneficial to the acquisition of language and literacy in kindergarten and preschool children and support storybook comprehension in 2-and 3-year olds [8,9].…”
Section: Introductionmentioning
confidence: 99%